Advancing Indigenous data governance through a shared understanding in Paulatuk, Inuvialuit Settlement Region - Drake, Allison K.; , Paulatuk Hunters and Trappers Committee; Green, Tony; Illasiak, Jody; Ruben, Bill S.; Ruben, Candace; Ruben, Lawrence; Dunmall, Karen M. (Frontiers in Environmental Science, 2025)
In the Canadian Arctic, we posit that locally-relevant Indigenous data governance frameworks are necessary in light of a paucity of guiding practices and policies for environmental researchers working in partnership with communities. To centre data governance decision-making in a community and to support Indigenous self-determination as affirmed in federal commitments, Fisheries and Oceans Canada researchers and the Paulatuk Hunters and Trappers Committee (Paulatuk, Inuvialuit Settlement Region) co-developed a data governance Statement of Shared Understanding for Traditional Knowledge Documentation specific to an interview project. We detail the steps and dialogue that characterized the creation of this statement over several months, so that others may build from these efforts when appropriate. Second, we highlight five emergent considerations that may strengthen future data governance efforts and inform policy, including: community and project context, the changing digital landscape, individual and collective knowledge protections, planned project outputs, and confidentiality and anonymity nuances. We offer these insights to advance evolving Indigenous data governance conversations, initiatives, and policies in institutional and community spaces.